A Histomorphological Study on the Tongue of Musk Deer (Moschus moschiferus) - Choudhury, A. R.; Khan, Massarat; Baba, M. A (Indian Journal of Veterinary Anatomy, 2013)
Tongue of four adult musk deer were processed for routine histomorphological observations. The study revealed that dorsal surface of the tongue was lined by stratified squamous keratinized epithelium. The tunica mucosa was studded with lingual papillae viz. filiform, lenticular, conical, fungiform and vallate papillae. Only a few taste buds were observed in fungiform and vallate papillae.Tunica muscularis made of skeletal muscle was arranged in three layers.